2011
DOI: 10.1128/mcb.01338-10
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF Complexes Containing Brahma or Brahma-Related Gene 1 Play Distinct Roles in Smooth Muscle Development

Abstract: SWI/SNF ATP-dependent chromatin-remodeling complexes containing either Brahma-related gene 1 (Brg1) or Brahma (Brm) play important roles in mammalian development. In this study we examined the roles of Brg1 and Brm in smooth muscle development, in vivo, through generation and analysis of mice harboring a smooth muscle-specific knockout of Brg1 on wild-type and Brm null backgrounds. Knockout of Brg1 from smooth muscle in Brg1 flox/flox mice expressing Cre recombinase under the control of the smooth muscle myosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…Both Brg1 and Brm are also known to interact with and stimulate the activity of several transcription factors, including the glucocorticoid receptor and C/EBP [16,17]. Other studies have suggested a functional redundancy between Brm and Brg1 [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Brg1 and Brm are also known to interact with and stimulate the activity of several transcription factors, including the glucocorticoid receptor and C/EBP [16,17]. Other studies have suggested a functional redundancy between Brm and Brg1 [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Brg1 binds to zinc finger protein through a unique N-terminal domain not present in Brm, while Brm interacts with two ankyrin-repeats proteins that are crucial in the Notch signal transduction [30]. More recently, studies have investigated the individual roles of Brg1 and Brm in various cellular processes, revealing again individual, cooperating, and redundant activities of these two proteins depending on the cell type and the specific context [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Brg1 is required for inhibition of apoptosis in the development of various cell types and organs, including neurons (Li et al, 2013), smooth muscle (Zhang et al, 2011) and blood cells (Griffin et al, 2008); consequently, knockout of Brg1 increases the rate of apoptosis in these tissues. Our data showing that elevated apoptosis was reversed by Notch1 ICD overexpression in VBN mice demonstrate that marked downregulation of Notch signaling is responsible for increased apoptosis in Brg1-deficient duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Brg1 is involved in apoptosis and cell proliferation during organ development (Griffin et al, 2008;Hang et al, 2010;Li et al, 2013;Seo et al, 2005;Zhang et al, 2011). Therefore, we next investigated whether the abnormal villous structure in Brg1-deficient duodenum was associated with changes in apoptosis or cell proliferation.…”
Section: Loss Of Brg1 Increases the Numbers Of Apoptotic And Prolifermentioning
confidence: 99%
See 1 more Smart Citation